Comprehensive Analysis of the Incidence and Survival Patterns of Lung Cancer by Histologies, Including Rare Subtypes, in the Era of Molecular Medicine and Targeted Therapy. Issue 24 (June 2015) - Chang, Jeffrey.S.; Chen, Li-Tzong; Shan, Yan-Shen; Lin, Sheng-Fung; Hsiao, Sheng-Yen; Tsai, Chia-Rung; Yu, Shu-Jung; Tsai, Hui-Jen; Chung., Chi-Jung
<x xml:space="preserve">Abstract</x> Abstract Lung cancer is the third most common cancer in the world and has the highest cancer mortality rate. A worldwide increasing trend of lung adenocarcinoma has been noted. In addition, the identification of epidermal growth factor receptor (EGFR) mutations and the introduction of EGFR inhibitors to successfully treat EGFR mutated non–small cell lung cancers are breakthroughs for lung cancer treatment. The current study evaluated the incidence and survival of lung cancer using data collected by the Taiwan Cancer Registry between 1996 and 2008. The results showed that the most common histologic subtype of lung cancer was adenocarcinoma, followed by squamous cell carcinoma, small cell carcinoma, large cell carcinoma, neuroendocrine tumors, lymphoma, and sarcoma. Overall, the incidence of lung cancer in Taiwan increased significantly from 1996 to 2008. An increased incidence was observed for adenocarcinoma, particularly for women, with an annual percentage change of 5.9, whereas the incidence of squamous cell carcinoma decreased. Among the subtypes of lung cancer, the most rapid increase occurred in neuroendocrine tumors with an annual percentage change of 15.5. From 1996–1999 to 2005–2008, the 1-year survival of adenocarcinoma increased by 10% for men, whereas the 1-, 3-, and 5-year survivals of adenocarcinoma for women increased by 18%, 11%, and 5%, respectively. Overall, the incidence of lung cancer has been increasing in Taiwan, although the trends were variable by subtype. The introduction of targeted therapies was associated with a significantly improved survival for lung adenocarcinoma in Taiwan; however, more studies are needed to explain the rising incidence of lung adenocarcinoma. In addition, it is important to investigate the molecular pathogenesis of the various subtypes of lung cancer to develop novel therapeutic agents.